Evaluation of Hemoglobin Cutoffs for Defining Anemia in a Multinational Sample of Healthy Individuals: The BRINDA Project (OR07-07-19). (13th June 2019) - Addo, Yaw; Yu, Emma Xinchun; Williams, Anne; Young, Melissa Fox; Sharma, Andrea; Mei, Zuguo; Jefferds, Maria Elena; Suchdev, Parminder
Abstract: Objectives: Current WHO hemoglobin (Hb) cutoffs (< 110 g/L, 6–59mo; < 120 g/L, 15–49y non-pregnant women) to define anemia were established in 1967 and validated in 1980 s among iron replete USA survey participants. Our objective was to examine the consistency of Hb cutoffs from multiple countries and age-variations in Hb concentrations among apparently healthy people using contemporary data. Methods: We analyzed altitude and smoking (women only)-adjusted Hb data from 25 countries for preschool children (PSC, 6–59mo, 24 surveys, n  = 35, 088) and women of reproductive age (WRA, 15–49y, 20 surveys, n  = 50, 846) from the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project. Healthy was defined as: [ferritin >12 µg/L (< 5y),  >15 µg/L ( >5y)], RBP or retinol >0.7 µmol/L, CRP ≤ 5 mg/L or AGP ≤ g/L, and no malaria (if measured)]. We examined Hb levels, cut-offs at specified percentiles (%ile) and country variations with age-adjusted generalized mixed models using country as random intercept. Results: The final analytic sample was 41, 314; the healthy inclusion criteria resulted in 17–88% data loss of the original data depending on country. Age and country-adjusted mean (SE) of Hb was 116.9 (1.44)g/L for PSC, and 129.1 (1.49)g/L for WRA and was significantly ( P  < 0.001) associated with age in PSC but not in WRA, and varied by country (pheterogeniety < .001, in each target group). Country explained 22% of the total Hb variance for each group. The pooled countries' Hb at the 5%ile was 94 g/L for PSC [range: 79 g/L (Pakistan) - 113 g/L (USA], and 110 g/L for WRA [92 g/L (Nigeria) - 121 g/L (USA)]. Conclusions: The high heterogeneity in Hb cutoffs among healthy people from different countries suggests that a single Hb cutoff for anemia may not work for every country. This multinational analysis suggests that different approaches may be warranted to establish Hb cutoffs. Funding Sources: Bill & Melinda Gates Foundation.